2009
DOI: 10.1002/ejoc.200900955
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Crystallographic Characterization of Allylindium Species Generated from Allyl Halide and Indium(0)

Abstract: The reaction of cinnamyl bromide with indium(0) gave two allylindium species, cinnamylindium dibromide and dicinnamylindium bromide. Either species were isolated after complexation of appropriate pyridine-type Lewis bases. The use of 3,5-dibromopyridine (Br 2 py) as a Lewis base gave cinnamylindium dibromide with two Br 2 py ligands. Dicinnamylindium bromide was isolated with 4-(dimethylamino)pyridine (Me 2 Npy) ligands. In both cases, the indium atom showed a trigonal-bipyramidal coordination sphere with the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…A relatively stable allylindium compound [cinnamylindium prepared from cinnamyl bromide (4) and In 0 ] was investigated in alcohol instead of water as a model reaction of diallylindium decomposition in water. The allylic species generated from cinnamyl bromide with indium(0) in THF, i.e., monoallylindium compound 5 and diallylindium compound 6, [8] were mixed with benzhydrol with stirring at room temperature for 30 min and analyzed by using NMR spectroscopy. [17] As expected, the monoallylindium compound 5 remained unchanged, and the diallylindium compound 6 was converted into the allylindium alkoxide 7 along with the generation of 3-phenylpropene (8) (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A relatively stable allylindium compound [cinnamylindium prepared from cinnamyl bromide (4) and In 0 ] was investigated in alcohol instead of water as a model reaction of diallylindium decomposition in water. The allylic species generated from cinnamyl bromide with indium(0) in THF, i.e., monoallylindium compound 5 and diallylindium compound 6, [8] were mixed with benzhydrol with stirring at room temperature for 30 min and analyzed by using NMR spectroscopy. [17] As expected, the monoallylindium compound 5 remained unchanged, and the diallylindium compound 6 was converted into the allylindium alkoxide 7 along with the generation of 3-phenylpropene (8) (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we used X-ray crystallographic analysis to determine the structures of the allylindium(III) species generated in organic solvents both by tin/indium transmetalation [7] and by reduction methods. [8] X-ray analysis required stabilization of the indium species by use of appropriate substituents on the allylic carbon chain and ligands to the indium center. [9,10] Many practical synthetic protocols use a reductive method in aqueous media to synthesize allylindium compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction of the in situ-generated allylindium compounds with benzaldehyde was monitored by NMR spectroscopy, and the results indicated that electronegative substituents retarded the nucleophilicity of the allylindium compounds. 5 This brief review summarizes recent advances in indiummediated, Barbier-type allylations of less-and un-polarized multiple bonds. We hope that the review will provide organic chemists with some insight in this field and serve as a helpful tool in designing synthetic strategies in their research.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, however, the chemistry of allylindium reagents has been rapidly growing, and widening their applicability in organic synthesis. A more in-depth understanding of the structure and reactivity of allylindium reagents has been established, 5 and various reactions of allylindium reagents have been reported with less-or un-polarized multiple bonds, 6e20 especially with nitrile group-containing substrates. 7b,21e26 Very recently, Baba and co-workers reported the isolation and crystallographic characterization of cinnamylindium species generated from cinnamyl bromide and indium metal for the first time (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation